Makna, emosi, dan identitas: Pengaruh karya Fiersa Besari terhadap literasi emosional generasi muda di era digital - Zanah, Rizka Riyatul (Maliki Interdisciplinary Journal, 2026)
This study examines meaning, emotion, and identity in the works of Fiersa Besari and their influence on the emotional literacy of young people in the digital era. The purpose of this research is to analyze how Fiersa Besari’s music, books, quotations, and reflective narratives function as a medium for self-understanding, emotional expression, and identity formation among youth. The method used is library research with a descriptive-qualitative approach through textual analysis of Fiersa Besari’s works, audience responses on social media, and relevant literature on popular culture and youth psychology. The findings show that Fiersa Besari’s works function not only as entertainment but also as reflective spaces for young people to recognize, name, and manage their emotions. His quotations help readers validate experiences of loss, sadness, and vulnerability. His music serves as a medium of catharsis and emotional healing, while his books encourage the search for life meaning and personal identity formation. On social media, his works have developed into collective symbols used in captions, travel videos, healing content, and other personal expressions. Furthermore, Fiersa’s narratives contain values of modern spirituality such as gratitude, acceptance, sincerity, and life journeys. This study confirms that popular culture can become an important medium of emotional learning for Indonesian youth and contribute to their psychological well-being and identity development in deeper and more sustainable ways.